East Asian Financial Safety Net : The Problem of Leadership - Pitakdumrongkit, Kaewkamol (2018)
A core challenge facing the advancement of a regional financial safety net in recent years has been an absence of leadership. Without such clear regional leadership, the future advancement of such a safety net — Chiang Mai Initiative Multilateralization (CMIM) – would be modest at best.